Legal Protection for Buyers in Land Sale and Purchase Agreements Underhand Where the Seller Commits Default During the Certificate Transfer Process - Abdulah, Taufik (TABELLIUS: Journal of Law, 2024)
The purpose of this study is to determine and analyze legal protection for buyers in land sale and purchase agreements underhand where the seller commits default during the certificate transfer process. To determine and analyze the obstacles for buyers in land sale and purchase agreements underhand where the seller commits default during the certificate transfer process and their solutions. The approach method used by the researcher is the case approach and the statutory regulatory approach. The type of research used is normative law. The data sources in this study are secondary data obtained from literature studies. Based on the results of the study, Legal Protection for Buyers in Land Sale and Purchase Agreements Underhand Where the Seller Commits Default During the Certificate Transfer Process. Repressively, namely with evidence of the agreement. This is regulated in Article 1866 of the Civil Code, and is emphasized in Article 1874 of the Civil Code which states that evidence can be a writing made underhand. Regarding the problem of buying and selling land underhand, a settlement can be made through litigation or non-litigation. Preventively, protection for buyers in implementing a land sale and purchase agreement is carried out with requirements and requests for irrevocable power of attorney. The obstacle is because when the buyer wants to carry out the name change process and look for the seller, it turns out that he is not found at his residence. The solution is, because the seller's whereabouts are not found, the buyer decides to file a lawsuit in the District Court.